Wire Splinting Treatment in Localized Chronic Periodontitis Patient: A Case Report - Maulani, Chaerita; Oktaviani, Anisa; Nurfianti (Lembaga Penelitian Universitas YARSI, 2025)
Introduction: Periodontal disease, characterized by inflammation of the tissues surrounding the teeth (such as the gingiva, cementum, alveolar bone, and periodontal ligament), is one of the most common problems. Periodontitis leads to the progressive destruction of the periodontal ligament and alveolar bone. As the disease progresses, attachment loss around the affected teeth, eventually increased tooth mobility. One treatment for stabilizing tooth mobility is splinting. Case Report: 37-year-old male patient, complaining of mobility in his lower teeth with multiple diastema. Wire splinting was performed on the patient using 0.3- and 0.4-sized wires from teeth 33 to 43. Discussion: Teeth mobility can cause masticatory dysfunction. Splinting preserves mobile teeth and serving as periodontal support. Splinting should leave area around the gingiva clean to avoid plaque accumulation and easy maintenance. Conclusion: Splinting in this case report, enabling the teeth to function properly and provide easy maintenance. A follow-up examination is required six months to a year later to assess the improvement of the alveolar bone.